2007
DOI: 10.1007/s11101-006-9032-2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites from species of the biocontrol agent Trichoderma

Abstract: Trichoderma species are free-living fungi that are highly interactive in root, soil and foliar environments and have been used successfully in field trials to control many crop pathogens. Structural and biological studies of the metabolites isolated from Trichoderma species are reviewed. This review, encompassing all the literature in this field up to the present and in which 269 references are cited, also includes a detailed study of the biological activity of the metabolites, especially the role of these met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
299
0
23

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(344 citation statements)
references
References 249 publications
(225 reference statements)
3
299
0
23
Order By: Relevance
“…Alguns autores mencionam que a ação sinergística atribuída à produção de enzimas e antibióticos, simultaneamente, possa explicar esse sucesso. O principal interesse é naqueles compostos que apresentam atividade antibiótica e que, provavelmente, estão implicados na eficácia do isolado em atuar como agente de biocontrole (22).…”
Section: Metabólitos Não Voláteis Vs Não-voláteis Termoestáveisunclassified
See 1 more Smart Citation
“…Alguns autores mencionam que a ação sinergística atribuída à produção de enzimas e antibióticos, simultaneamente, possa explicar esse sucesso. O principal interesse é naqueles compostos que apresentam atividade antibiótica e que, provavelmente, estão implicados na eficácia do isolado em atuar como agente de biocontrole (22).…”
Section: Metabólitos Não Voláteis Vs Não-voláteis Termoestáveisunclassified
“…Dentre os metabólitos produzidos por Trichoderma spp. citam-se: ácido harziânico, alameticinas, antraquinonas, azafilonas, daucanas, harzialactonas, bisorbicillinoides, butenolides, tricholina, glisopreninas, ácido heptelídico, gliovirina, pironas, tricotecenos, isocianatos, trichosetina, viridina, peptaiboles, entre outros (18,22). Tais metabólitos, cuja produção é atribuída a vários genes, são excretados nas fases de crescimento e esporulação e estão entre os produtos naturais mais importantes utilizados para inibir o crescimento de microrganismos (3,30).…”
Section: Introductionunclassified
“…The emerging regulatory elements that influence the CSSR provide us with good opportunities to manipulate the behaviour of fungi during carbon starvation. Increasing the production of antibiotics and antimycotics is important in the fermentation industry but can also enhance the efficiency of biocontrol agents (Reino et al, 2008). Inhibition of mycotoxin formation is crucial in food and pharmaceutical fermentations or during post-harvest decay of food and animal feed (Edlayne et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As antagonists of other fungi, Trichoderma are the most widely used biofungicides (Verma et al, 2007;Lorito et al, 2010). They also produce numerous secondary metabolites, including potential antibiotics and anti-cancer compounds (Reino et al, 2008). Research in the past decade has revealed that Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%